Dissecting the Influence of Carbon Emissions on Firm Value: The Strategic Role of Stock Returns as a Mediating Variable - Kodriyah Kodriyah; Santi Octaviani (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effects of Carbon Emission Disclosure (CED), liquidity, and leverage on firm value, as well as to examine the role of stock returns as a mediating variable. A quantitative research method was employed, utilizing multiple regression and path analysis on data from companies listed on the Indonesia Stock Exchange, particularly within sectors related to environmental issues. The findings indicate that CED significantly affects firm value both directly and indirectly through stock returns. Stock returns also demonstrate a significant positive effect on firm value. In contrast, liquidity and leverage do not exhibit significant effects, either directly or when mediated by stock returns. These results suggest that investors respond more to non-financial information, especially sustainability disclosures, than to traditional financial indicators. This study implies that companies should enhance the quality of their CED reporting as a strategy to build investor trust and sustain long-term firm value. This study is limited to companies listed on the Indonesia Stock Exchange, focusing mainly on environmentally related sectors, which may limit the generalizability of the results to other industries or geographical contexts. Moreover, reliance on quantitative methods and secondary data may overlook qualitative perceptions of stakeholders. Future research is recommended to expand sampling across diverse industries and regions to validate these findings further. Incorporating qualitative approaches could provide deeper insights into investor reactions to carbon emission disclosures. Companies are encouraged to adopt more transparent and standardized carbon emission disclosure practices and integrate sustainability into their broader strategic management to effectively enhance firm value.